MANAJEMEN PRODUKSI PROGRAM “MOJOK MENTOK” MEDIA ONLINE MOJOK.CO PADA TAHUN 2022/2023 - Zakiy Fatih, Muhammad Ghulam; Winata, Muhammad Danu (The Commercium, 2024)
Research on program production management is an interesting research. In this study, researchers chose the "Mojok Mentok" program which was broadcast through online media Mojok.co in 2022/2023. Mojok.co or PT. Narasi Akal Jenaka is an online media located at Perum Sukoharjo Indah A8 RT 09 RW 16 Dukuh Purworejo Sukoharjo Village, Ngaglik Sleman, D.I. Yogyakarta. Researchers chose the "Mojok Mentok" program because it has a uniqueness in the process of delivering news which is delivered lightly and spiced with humor. This research uses a qualitative descriptive approach using the 6M theory by George Terry as its conceptual framework. This research method involves direct observation, interviews with the production team, and analysis of program content. The collected data was analyzed using an inductive approach to identify patterns, challenges, and production management practices used in the creation of the "Mojok Mentok" program. The results showed that the production management of this program involves strong coordination between various elements, including people, methods, machines, materials, money, and markets as described in 6M theory. These findings provide deep insights into how the production management of online media programs can be applied in practice, as well as contribute to the further development of media production management theory.